Comparative clinical trial of epsilon amino-caproic acid and tranexamic acid in the prevention of early recurrence of subarachnoid haemorrhage. Issue 9 (September 1981) - Chowdhary, U M; Sayed, K
Abstract : A comparative controlled clinical trial of epsilon aminocaproic acid (EACA), 36 g/day and tranexamic acid (TEA), 6 g/day, was undertaken to assess their effectiveness in reducing early recurrence of subarachnoid haemorrhage (SAH). Of 90 patients treated with EACA recurrent haemorrhage was seen in 8% of these patients and 7% of the patients developed delayed ischaemic deficit. The total pre-operative mortality in EACA-group was 11%. Of 61 patients treated with TEA, 10% had recurrent haemorrhage and delayed ischaemic deficit occurred in 5% of the patients. The total pre-operative mortality in TEA-group was 11%. No difference was found between the effectiveness and side-effects of these drugs.